2016
DOI: 10.1038/srep28472
|View full text |Cite
|
Sign up to set email alerts
|

‘Squeezing’ near-field thermal emission for ultra-efficient high-power thermophotovoltaic conversion

Abstract: We numerically demonstrate near-field planar ThermoPhotoVoltaic systems with very high efficiency and output power, at large vacuum gaps. Example performances include: at 1200 °K emitter temperature, output power density 2 W/cm2 with ~47% efficiency at 300 nm vacuum gap; at 2100 °K, 24 W/cm2 with ~57% efficiency at 200 nm gap; and, at 3000 °K, 115 W/cm2 with ~61% efficiency at 140 nm gap. Key to this striking performance is a novel photonic design forcing the emitter and cell single modes to cros resonantly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 56 publications
1
58
0
Order By: Relevance
“…Recently, the far-field TR performance was theoretically analyzed by Strandberg [3], and was demonstrated experimentally by Santhanam and Fan [5] with a relatively low achieved efficiency. Motivated by thermophotovoltaic (TPV), where an emitter is placed between the heat source and the cold PV cell to reshape the photon emission spectrum [7][8][9][10][11][12][13][14][15], placing a heat sink between the hot TR cell and the cold environment is shown to enhance the performance of TR devices [6,16,17]. Using the impedance matching condition derived from Coupled-Mode Theory [18][19][20][21][22][23][24][25], it is shown that the emitter and the PV cell in the near-field setup should be designed as a whole to maximize the radiative energy transfer and therefore the power output [15,24,26].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the far-field TR performance was theoretically analyzed by Strandberg [3], and was demonstrated experimentally by Santhanam and Fan [5] with a relatively low achieved efficiency. Motivated by thermophotovoltaic (TPV), where an emitter is placed between the heat source and the cold PV cell to reshape the photon emission spectrum [7][8][9][10][11][12][13][14][15], placing a heat sink between the hot TR cell and the cold environment is shown to enhance the performance of TR devices [6,16,17]. Using the impedance matching condition derived from Coupled-Mode Theory [18][19][20][21][22][23][24][25], it is shown that the emitter and the PV cell in the near-field setup should be designed as a whole to maximize the radiative energy transfer and therefore the power output [15,24,26].…”
Section: Introductionmentioning
confidence: 99%
“…The optical parameters of GaSb are calculated using a universal model for III–V semiconductors 25 . The emitter was chosen to be a plasmonic material with its plasmonic frequency slightly above the cell’s bandgap, which enables strong surface wave excitations in the designated frequency range to maximize the radiative transfer efficiency 11 . In this work, the optical parameters are taken from the experimental data of Ga:ZnO (GZO) 26 , which has an near-infrared (NIR) plasmonic frequency (1.38 × 10 15  rad/s) and high melting point to suit the requirement for a TPV emitter.…”
Section: Resultsmentioning
confidence: 99%
“…These values lead to surface polariton resonance at 0.85 eV when sharing an interface with vacuum. This is similar to real materials such as titanium carbide (TiC) and tantalum silicide (TaSi 2 ) which have resonances at 0.9 eV and 0.8 eV, respectively [33]. The device is assumed to be azimuthally symmetric and infinite in the ρ -direction making the view factor unity between the emitter and the cell.…”
Section: Description Of the Problemmentioning
confidence: 90%